First Encounters With Instructors. Issue 2 (June 2015) - Shahsavari, Hooman; Parsa-Yekta, Zohreh; Houser, Marian L.; Ghiyasvandian, Shahrzad
ABSTRACT Background: The first encounter between an instructor and his/her student influences the development of their mutual relationship. This phenomenon has received little attention in the literature within the context of nursing education. Purpose: This study explores and describes qualitatively the subjective experience and perceptions of nursing students related to their first encounter with instructors in both classroom and clinical settings. Methods: A purposeful sampling method was utilized to select 15 nursing students from a nursing school in Iran to participate in semistructured interviews. Data were analyzed using a qualitative content analysis approach. Results: Data analysis identified three main themes: (a) preexisting expectations, with the four subthemes of socially shared expectations, personal expectations, profession-related expectations, and reputation-directed expectations; (b) student's judgment, with the three subthemes of assessing the instructor, assessing criteria, and good or bad beginning; and (c) future interactions, with the two subthemes of constructive decisions and destructive decisions. Conclusions/Implications for Practice: The results show that the initial student–instructor encounter is a process in which students rely heavily on preexisting expectations to assess and judge the initial interaction with their instructor. The findings of this study may help nursing instructors in various national and cultural settings increase their awareness of the factors that influence their first encounters with students. Greater awareness may help positively shape student perspectives of the instructor's role and encourage students to collaborate with the instructor in the teaching and learning process in order to create a better outcome for both.